An Analysis of Merdeka Curriculum Implementation in Indonesia: A Case Study of Facilitating Students’ Transformation - Juniriang Zendrato; Dorothy Christabelle Agatha (UKI Press, 2023)
Merdeka Curriculum for the academic year 2022-2024 has been issued by the Indonesian government to overcome the learning loss at schools due to Pandemic-Covid 19. There are some challenges in the implementation, one of which is teachers’ lack of understanding of the meaning and purpose of the Merdeka curriculum. It causes students’ boredom with learning in the classroom. Therefore, the research, which applies the qualitative approach with case study procedures, aims to offer interactive teaching as a solution to apply the Merdeka curriculum after analyzing its implementation. The result is Merdeka Curriculum gives freedom to the students in learning. In running the curriculum, Christian teachers base their philosophy on the Bible. Christian teaching will bring the students to experience life transformation. Therefore, interactive teaching is chosen to be implemented, because it gives freedom to teachers to design the learning based on the Biblical Christian Worldview and to students to learn in the Shalom class community. In conclusion, teaching learning that is done biblically will facilitate students’ transformation. For future researchers, they can research on how Christian teachers respond to the Merdeka Curriculum based on their school contexts and ground their teaching on the Bible to facilitate students’ life transformation.